2008
DOI: 10.1094/phyto-98-12-1340
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infection by Two Criniviruses Alters Accumulation of Each Virus in a Host-Specific Manner and Influences Efficiency of Virus Transmission

Abstract: Tomato chlorosis virus (ToCV), and Tomato infectious chlorosis virus (TICV), family Closteroviridae, genus Crinivirus, cause interveinal chlorosis, leaf brittleness, and limited necrotic flecking or bronzing on tomato leaves. Both viruses cause a decline in plant vigor and reduce fruit yield, and are emerging as serious production problems for field and greenhouse tomato growers in many parts of the world. The viruses have been found together in tomato, indicating that infection by one Crinivirus sp. does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 26 publications
3
95
1
5
Order By: Relevance
“…However, just focusing on plant viruses, the same interaction described here has been observed for several other pairs of viruses (Hii et al, 2002;Kokkinos & Clark, 2006;Zeng et al, 2007;Wintermantel et al, 2008). In other interactions, however, both viruses gain an advantage (Scheets, 1998;Hii et al, 2002), both viruses pay a cost (Wintermantel et al, 2008), one of them gains whereas the other is not apparently affected (Wang et al, 2002(Wang et al, , 2004Wege & Siegmund, 2007) or one pays a cost whilst the other remains unaffected (Pohl & Wege, 2007).…”
Section: Biological Game Between Tumv and Camv Predicts Exclusion Of supporting
confidence: 76%
See 2 more Smart Citations
“…However, just focusing on plant viruses, the same interaction described here has been observed for several other pairs of viruses (Hii et al, 2002;Kokkinos & Clark, 2006;Zeng et al, 2007;Wintermantel et al, 2008). In other interactions, however, both viruses gain an advantage (Scheets, 1998;Hii et al, 2002), both viruses pay a cost (Wintermantel et al, 2008), one of them gains whereas the other is not apparently affected (Wang et al, 2002(Wang et al, , 2004Wege & Siegmund, 2007) or one pays a cost whilst the other remains unaffected (Pohl & Wege, 2007).…”
Section: Biological Game Between Tumv and Camv Predicts Exclusion Of supporting
confidence: 76%
“…Detection techniques used in most previous reports on mixed infections have been aimed at comparing the accumulation of each competing virus in singly versus coinfected plants, but to our knowledge, relative accumulation among competing viruses has been estimated only in a few instances (Scheets, 1998;Kokkinos & Clark, 2006;Zeng et al, 2007;Wintermantel et al, 2008). To determine an estimate of the relative fitness of our competing viruses, TuMV was titrated by RT-qPCR and CaMV by qPCR using an absolute quantification method.…”
Section: Co-infection Exerts Opposite Effects On Tumv and Camv Accumumentioning
confidence: 99%
See 1 more Smart Citation
“…In an individual host, coinfection may have variable consequences, from the development of milder symptoms to their exacerbation (Hammond et al, 1999). Mixed infections also affect traits such as the host range (García-Cano et al, 2006;Guerini & Murphy, 1999;Hacker & Fowler, 2000), the rate of transmission (Wintermantel et al, 2008), cellular tropism (Moreno et al, 1997;Sánchez-Navarro et al, 2006), or viral accumulation (Martín & Elena, 2009). …”
Section: Mixed Infections and Among-virus Interactionsmentioning
confidence: 99%
“…Even if no general trend arises from results concerning viral mutant genotypes, such studies demonstrate the existence of variation in the relationships between viral accumulation and virulence or symptom severity. Unfortunately, studies that reported the phenotype of natural isolates often measured only virulence (Yahara & Oyama 1993;Lapidot et al 1997;Maskell et al 1999;Funayama-Noguchi 2001;Malmstrom et al 2005Malmstrom et al , 2006 or viral accumulation (Fargette et al 1987;Llamas-Llamas et al 1998;Thurston et al 2001;Untiveros et al 2007;Wintermantel et al 2008) of one viral isolate in one or several host genotypes in different environments. To our knowledge, only a handful of studies have measured both phenotypes concomitantly for several viral natural isolates after individual inoculation of one host genotype.…”
Section: Viral Accumulation Versus Virulencementioning
confidence: 99%